P170 Single centre experience on idiopathic pulmonary fibrosis patient tolerance of pirfenidone; impact on nurse-led ILD helpline usage. (15th November 2016) - Rathnapala, A; Ruggiero, C; Fries, A; Ho, LP; Hoyles, RK
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a progressively scarring lung disease with a poor prognosis. The anti-fibrotic agent Pirfenidone slows FVC decline and reduces mortality. Side-effect management is critical to help patients remain on treatment. Objectives: To examine tolerance to Pirfenidone in our specialist ILD centre: to identify the prevalence, nature and management of adverse effects, and the impact on the ILD nurse-led helpline. Methods: In this retrospective study, all patients with an ILD MDT diagnosis (ATS/ERS) of IPF treated with Pirfenidone for >3 months were included. Data was derived from the patient records and nurse-led ILD helpline logs. Results: 100 patients were treated with Pirfenidone Feb 2012–July 2016. 16 patients were excluded (<3 months' treatment (n = 7), death <1 month (n = 2), other (n = 7), 84 remained in the study; Definite: Probable IPF 47:37, male: female 68:16, average age 73.7 (40–88). 72 (85.7%) experienced at least one adverse effect; appetite/weight loss (n = 39, 34.5%), nausea (n = 26, 23%), diarrhoea (n = 17, 15%), fatigue (n = 11, 9.7%), photosensitivity (n = 11, 9.7%), skin rash (n = 9, 8%). No patients required side-effect-related hospital admission. Management: treatment pause (n = 36, 50%), dose reduction alone (n = 15, 20.8%), initial reduction and subsequent pause (n = 4, 5.6%). n = 17 (23.6%) with mild side-effects were managed with advice alone (dose unchanged). Of those with dose reductions/pause (n = 55), 21 (38%) were gradually re-escalated to full dose, 1 (2%) continued on reduced dose. Pirfenidone was discontinued and offered symptom-based management in n = 17 (31%), (unable to switch to Nintedanib due to FVC < 50% (7), not preferred (3), bleeding risk (2), other (5)), while n = 16 (29%) were able to switch to Nintedanib. Impact on the nurse-led helpline was assessed in n = 45 (unselected subset); > 82% used the helpline, often initiated due to side-effects; patients with deteriorating symptoms or end-stage disease engaged most frequently. Conclusions: In this real-life study, we found a higher prevalence of side effects than previously described. Nurse-led helpline use was often initiated by side effect concerns, but usage broadened into more holistic support as the nurse patient relationship developed. In response, the Oxford ILD Service has initiated a side-effect management protocol with more cautious (than standard) initial escalation and re-challenging regime.